Level of protein for heifer calves wintered on bluestem pasture - DeGeer, C.V.; Smith, E.F.; Richardson, D.; Good, D.L. (Kansas Agricultural Experiment Station, 2011)
The 65 heifers used in this study were good-to-choice Herefords purchased near Fort Davis, Texas, assigned to treatments on a random-weight basis. The heifers were rotated between pastures so any differences due to pastures were minimized. Dicalcium phosphate was fed to standardize phosphorus intake between groups.
Keywords: Beef; Protein; Dicalcium phosphate; Performance